Concurrent validity of the CORE wearable sensor with BodyCap temperature pill to assess core body temperature during an elite women`s field hockey heat training camp - Goods, P. S. R.; Maloney, P.; Miller, J.; Jennings, D.; Fahey-Gilmour, J.; Peeling, P.; Galna, B. (European Journal of Sport Science, 2023)
Wearable temperature sensors offer the potential to overcome several limitations associated with current laboratory- and field-based methods for core temperature assessment; however, their ability to provide accurate data at elevated core temperatures (Tc) has been questioned. Therefore, this investigation aimed to determine the concurrent validity of a wearable temperature sensor (CORE) compared to a reference telemetric temperature pill (BodyCAP) during a team-sport heat training camp prior to the 2020 Olympic Games. Female field hockey players (n = 19) in the Australian national squad completed 4 sessions in hot conditions where their temperature was monitored via CORE and BodyCAP. Concurrent validity of the wearable CORE device was determined with reference to the ingested BodyCAP pill. Lin`s Concordance Correlation Coefficients determined there was "poor" agreement between devices during all sessions. Mean bias demonstrated that CORE underestimated Tc in all sessions (-0.06°C to -0.34°C), with wide mean 95% confidence intervals (±0.35°C to ±0.56°C). Locally estimated scatterplot smoothing regression lines illustrated a non-linearity of error, with greater underestimation of Tc by the CORE device, as Tc increased. The two devices disagreed more than ±0.3°C for 41-60% of all data samples in each session. Our findings do not support the use of the CORE device as a valid alternative to telemetric temperature pills for Tc assessment, particularly during exercise in hot conditions where elevated Tc are expected.